Chronic kidney disease acquired knowledge in a diabetic and hypertensive population using a translated and validated questionnaire - Rogelio Maya-Quinta; Gloria P. Rodriguez-Gomez; Raul Del Toro-Mijares; Fanny Henriquez-Santos; Alexandro J. Martagon (Renal Failure, 2023)
Chronic kidney disease (CKD) is the progressive and irreversible functional and/or structural impairment of the kidney; its main etiologies include hypertension and diabetes. Mexico has the second highest prevalence of CKD worldwide with a high economic burden affecting public and private health systems. Patients with higher knowledge about CKD increase their adherence to preventive treatment. In this study we aim to describe the knowledge of CKD in a sample of Mexican high-risk population, comparing it with general Mexican population, medical students and nephrologists. A cross-sectional, observational study was performed divided in two phases: translation and validation of the knowledge questionnaire to Spanish, and cross-sectional survey to evaluate the knowledge of CKD in patients with diagnosis of diabetes and/or hypertension. We interviewed medical students, general population, and nephrologists to attain validation of the questionnaire in Spanish. The questionnaire was answered by 1,061 participants within the high-risk population. The results of the questionnaire were: 22/24, 18/24, 13.8/24, and 13.4/24 in nephrologists, medical students, normal subjects, and high-risk population, respectively. The questions with least correct answers were related to kidney functions and CKD risk factors. To our knowledge this is the first time a questionnaire for CKD knowledge is applied in Mexican population. These findings suggest poor understanding of kidney functions, risk factors, and symptoms of CKD. It is important not only to provide medical treatment to chronic illness but also awareness of the consequences of not achieving goals of treatment.